Trends in scientific research on climate change in agriculture and forestry subject areas (2005–2014) - Aleixandre-Benavent, R.; Aleixandre-Tudó, J.L.; Castelló-Cogollos, L.; Aleixandre, J.L. (Journal of cleaner production, 2017)
The term “Climate change” involves an alteration of the mean and variability of the climate properties. It implies unusual variations in the planet earth atmosphere, which causes related effect on other parts of the planet. The reduction in the land crops annual yield is derived from those alterations. The objective of this paper was to contribute to a better understanding of the scientific knowledge of climate change and its effect concerning agriculture and investigate its evolution through published papers. The items under study were obtained from the Web of Science (WOS) platform from Thomson Reuters. A bibliometric and social network analysis was performed to determine the indicators of scientific productivity, impact and collaboration between authors, institutions and countries. A subject analysis taking into account the key words assigned to papers and subject areas of journals was also carried out. A total of 1471 articles were included in the selected subject categories in WOS from 2005 until 2014. More than 50% of the papers were published in the last three years. The papers were published in 302 different journals. The United States Department of Agriculture (USDA) is the most productive institution (n = 70), followed by the Chinese Academy of Sciences (n = 58) and the Institut National de la Recherche Agronomique (INRA, France) (n = 47). The Canadian Forest Service has the most citations (n = 1456). The most frequent keywords were CO2, adaptation, model, temperature and impact. The network of collaboration between institutions and countries involve both centres from developed and developing countries and the central position of the United States, together with other leading countries, such as China, Canada, Australia, Germany, and the United Kingdom. Twenty papers received more than 100 citations, most of them concerned with emerging risks that climate change causes on forests, the impact on the forest ecosystems, the effect on plant diseases and adaptation options. •Climate change reflects abnormal variations on crops lands and reveal the risk on forest ecosystems.•This study contribute to a better understanding of the scientific knowledge in climate change and it’s effect.•The network of collaboration between countries shows the central position of the United States.•This work has provided helpful insights into the climate change research in agriculture and forestry subject areas.